Study of unripe and inferior banana flours pre-gelatinized by four different physical methods - Zhang, Siwei; Zhao, Kangyun; Xu, Fei; Chen, Xiaoai; Zhu, Kexue; Zhang, Yanjun; Xia, Guanghua (Frontiers in Nutrition, 2023)
This study aimed to prepare the pre-gelatinized banana flours and compare the effects of four physical treatment methods (autoclaving, microwave, ultrasound, and heat-moisture) on the digestive and structural characteristics of unripe and inferior banana flours. After the four physical treatments, the resistant starch (RS) content values of unripe and inferior banana flours were decreased from 96.85% (RS2) to 28.99–48.37% (RS2 + RS3), while C∞ and k values were increased from 5.90% and 0.039 min−1 to 56.22–74.58% and 0.040–0.059 min−1, respectively. The gelatinization enthalpy (ΔHg) and I1047/1022 ratio (short-range ordered crystalline structures) were decreased from 15.19 J/g and 1.0139 to 12.01–13.72 J/g, 0.9275–0.9811, respectively. The relative crystallinity decreased from 36.25% to 21.69–26.30%, and the XRD patterns of ultrasound (UT) and heat-moisture (HMT) treatment flours maintained the C-type, but those samples pre-gelatinized by autoclave (AT) and microwave (MT) treatment were changed to C + V-type, and heat-moisture (HMT) treatment was changed to A-type. The surface of pre-gelatinized samples was rough, and MT and HMT showed large amorphous holes. The above changes in structure further confirmed the results of digestibility. According to the experimental results, UT was more suitable for processing unripe and inferior banana flours as UT had a higher RS content and thermal gelatinization temperatures, a lower degree and rate of hydrolysis, and a more crystalline structure. The study can provide a theoretical basis for developing and utilizing unripe and inferior banana flours.